Keragaman Waktu Tanam Tanaman Padi di Pulau Kalimantan - Eleonora Runtunuwu (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
Rice planting time varied among farming sites. This research was aimed to study the variation in planting time especiallyin rainy season in Kalimantan. ‘Planting time’ was deterimined using assumption as the time when 8% of paddy fields ina sub district had been planted. Analysis was done by using mean ten-days of planting area of each sub-district during theperiod of 2000 to 2009 that was obtained from Statistics Indonesia. The result showed that the farmers in Kalimantan startedplanting rice during the first and second ten-days of September each year. Peak time of rice planting varied among provinces,i.e., on October II/III (West Kalimantan), January I/II and June II/III (East Kalimantan), and March III/April I (South andCentral Kalimantan). Data from this research could be used to calculate planting management at national level.Keywords: paddy crop, planting area, planting time, rain fall